Multi-directional radiation detector using photographic film - Junet, Laila Kalidah; Abdul Majid, Zafri Azran; Sapuan, Abdul HaliM; Sayed, Inayatullah Shah; Pauzi, Nur Farahana (Institute of Physics Publishing (UK), 2014)
Ionising radiation has always been part of our surrounding and people are continuously exposed to it. Ionising radiation is harmful to human health, thus it is vital to monitor the radiation. To monitor radiation, there are three main points that should be observed cautiously, which are energy, quantity, and direction of the radiation sources. A three dimensional (3D) dosimeter is an example of a radiation detector that provide these three main points. This dosimeter is able to record the radiation dose distribution in 3D. Applying the concept of dose detection distribution, study has been done to design a multi-directional radiation detector of different filter thicknesses. This is obtained by designing a cylinder shaped aluminum filter with several layers of different thickness. Black and white photographic material is used as a radiation-sensitive material and a PVC material has been used as the enclosure. The device is then exposed to a radiation source with different exposure factors. For exposure factor 70 kVp, 16 mAs; the results have shown that optical density (OD) value at 135 degree is 1.86 higher compared with an OD value at 315 degree which is 0.71 as the 135 degree area received more radiation compare to 3150 region. Furthermore, with an evidence of different angle of film give different value of OD shows that this device has a multidirectional ability. Materials used to develop this device are widely available in the market, thus reducing the cost of development and making it suitable for commercialisation.